Blue light filtering ophthalmic lenses: A systematic review. (3rd October 2021) - Vagge, Aldo; Ferro Desideri, Lorenzo; Del Noce, Chiara; Di Mola, Ilaria; Sindaco, Daniele; Traverso, Carlo E.
ABSTRACT: Background : Blue blocking (BB) lenses, including spectacles and intraocular lenses, work by attenuating short-wavelength light. BB glasses are being marketed with the aim to reduce eye fatigue symptoms when using digital devices, improve sleep quality and potentially confer protection from retinal phototoxicity. BB intraocular lenses following cataract surgery may be implanted because they are thought to prevent age-related macular degeneration (AMD) progression. Methods : The present study is a systematic review aiming to analyze BB lenses clinical efficacy in preventing blue light-related ocular disorders, including AMD progression, eye fatigue, and their impact on sleep quality. We searched Medline, PubMed, Web of Science and the Cochrane Library until May 2020. Results :Although several studies have been performed investigating BB lenses, clinical efficacy for preventing or attenuating the above-mentioned ocular disorders is often theorical or based on laboratory or animal experiments. Conclusions: To date, there is a lack of consistent evidence for a larger-sclale introduction of BB lenses in the routine clinical practice.